Front-of-pack food labeling in South America: A scoping review (Research, Society and Development, 2024)
The aim of the study was to map and synthesize the scientific production of knowledge regarding front-of-package food labeling in South American countries. A scoping review was conducted in 2023, based on the Joanna Briggs Institute guide, using a search strategy across five electronic databases: LILACS, SciELO, PubMed, Web of Science, and Scopus, with no restrictions on language or year of publication. The analysis process was carried out through blinded review by two reviewers: 1) article selection using the Rayyan platform, 2) data extraction using a standardized form, 3) PRISMA flowchart and checklist, 4) frequency calculations, and organization of findings. The search strategy identified 2,711 records, of which 94 articles met the inclusion criteria. There was a prevalence of studies from Uruguay and from the year 2020; 61% of the studies were cross-sectional observational, and 57% had a local scope. Study outcomes addressed the nutritional quality and composition of foods, the food industry, types of labeling, and consumer food choices. The synthesis revealed heterogeneity in results regarding the effectiveness of labeling types and the nutritional quality of packaged foods due to different populations studied. The mapping allowed the identification of resistance from the food industry to policy implementation, even in the face of evidence of improved consumer food choices, regardless of the type of front-of-package labeling used. It is suggested that new studies investigate different labeling methodologies more robustly across different countries.